Kebijakan Pemerintah Kota Makassar Dalam Pembinaan Gelandangan Di Kota Makassar - Ambo Masse; Abdul Sahid (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
Urbanization has been rapidly increased to Makassar the cities, In the other hand, the job opportunities in the cited cities have not fully fitted those who urbanize, thus bring them to be homeless.This research is a kualitatif descriptive taking a sample of 100 out of 269 homeless in Makassar city with using non random (purposive sampling) technique. The research pointed out that there are some reasons of being homeless, namely internal and external factors. These factors could be partially and mutually influenced the homeless. Internal factors consist of (i) the low of education; (ii) personality. Meanwhile, the external factors are : (i) urbanitation; (ii) environment; (iii) geographys; and (iv) economy.The alternative solutions should be comprehensively paid attention to the two aspects (i) namely the village condition and (ii) destination cities conditions. It is principally that the solutions should be able to protect them leaving their village to look for job in the cities by opening job opportunities in the village itself. Meanwhile, the homeless in the cities should be handled by making them have no chance to gain money as homeless.